Digitalisierung als Chance und Herausforderung - Bemerkungen aus der Didaktik der Informatik - Schulte, Carsten; Winkelnkemper, Felix (Theologie im Übergang - Identität - Digitalisierung - Dialog)

SUPPORTING GEOMETRY LEARNING DIGITALLY THROUGH ADAPTABLE ALGORITHMIC FEEDBACK-CHALLENGES AND SOLUTIONS - Huhmann, Tobias; Winkelnkemper, Felix (EDULEARN22 Proceedings)

Pentomino Digital - Mit Einer App Geometrie Lernen - Huhmann, Tobias; Eilerts, Katja; Winkelnkemper, Felix (Mathematik differenziert)
Keywords: ⛔ No DOI found

Multiscale analysis of composite structures with goal-oriented mesh adaptivity and reduced order homogenization - Ju, Xiaozhe; Mahnken, Rolf; Xu, Yangjian; Liang, Lihua; Cheng, Chun; Zhou, Wangmin (Composite Structures)
Keywords: Civil and Structural Engineering; Ceramics and Composites

Ausbildung in der zweiten Phase der Lehrerbildung. - Tenberge, Claudia (Professionalisierung von Grundschullehrkräften.)

Holz erleben. Technik verstehen. - Möller, Kornelia; Eikmeyer, Birgit; Tenberge, Claudia; Wilke, Torben; Zolg, Monika

Effect of diffusivity and chemical reactions on the determination of mass transfer coefficients in columns with structured packing - Mapura, Luz Alejandra; Kenig, Eugeny Y. (Annual Meeting on Reaction Engineering and ProcessNet Subject Division "Heat and Mass Transfer")

Experimental study on the condensation of pure substances in outer pillow-plate channels - Buckmann, Felix; Kenig, Eugeny (Annual Meeting on Reaction Engineering and ProcessNet Subject Division "Heat and Mass Transfer")

Pre-Service Teachers’ Collaborative Lesson Planning and their Self-Concepts in Inclusive Education. Single Paper. EARLI SIG 11 Conference 2022 ‘Teaching and Teacher Education’. “Digital Transformation in Teaching and Teacher Education” - Schulze, Jan Roland; Blumberg, Eva; Hellmich, Frank

Schöpfen, gautschen, trocknen. Wassereinsatz in der Papierherstellung. - Tenberge, Claudia (Grundschule Sachunterricht.)

Theorien und Konzeptionen inklusiven Sachunterrichts - Schröer, Franz; Tenberge, Claudia (Inklusive (Fach-)Didaktik in der Primarstufe - Ein Lehrbuch)
Das Lehrbuch umfasst Beiträge zur Einführung in den Inklusionsdiskurs, zu Modellen der Allgemeinen Didaktik und der inklusiven Didaktik, zur praxeologischen Unterrichtsforschung, zum Mathematik-, Deutsch-, Sach-, Kunst-, Religions-, Englisch- und Sportunterricht sowie Kommentare zum Zusammenhang der aufgeführten Themenbereiche.

Future Primary Teacher Education: Computational Thinking and STEAM. - Lenke, Michael; Tenberge, Claudia

Über die Dächer der Welt. - Tenberge, Claudia (Grundschule Sachunterricht.)

Determinants for students’ attitudes towards peers with non-compliant classroom behavior in inclusive primary schools. Single Paper Presentation. AERA (American Educational Research Association) 2022. Annual Meeting Theme: „Cultivating Equitable Education Systems for the 21^st Century“, Roundtable Session: "Focus on Behavior in Special and Inclusive Education" - Löper, Marwin Felix; Lehofer, Mike; Schwab, Susanne; Hellmich, Frank

Do primary school students’ contact experiences matter for their attitudes towards peers with special needs? Single Paper. 10th SELF International Conference. “SELF in Focus: Leading Research Perspectives and Applications in an Exciting New Age of Science” - Löper, Marwin Felix; Lehofer, Mike; Schwab, Susanne; Hellmich, Frank

Primary school students’ social self-concepts, their empathy and their attitudes towards peers with social and emotional difficulties. Single Paper. 10th SELF International Conference. “SELF in Focus: Leading Research Perspectives and Applications in an Exciting New Age of Science” - Löper, Marwin Felix; Hellmich, Frank

Elementary school teachers' self-efficacy beliefs concerning inclusive education. Single Paper Presentation. AERA (American Educational Research Association) 2022. Annual Meeting Theme: „Cultivating Equitable Education Systems for the 21^st Century“ - Franzen, Katja; Moschner, Barbara; Hellmich, Frank

Primary school students’ attitudes towards peers with special educational needs – First findings of an intervention program for the promotion of students’ social participation. Symposium “Let’s be friends! The importance of social inclusion in the lives of children and adolescents” (Sepideh Hassani). ECER (European Conference on Educational Research) 2022 PLUS. “Education in a Changing World: The impact of global realities on the prospects and experiences of educational research” - Görel, Gamze; Löper, Marwin Felix; Hellmich, Frank

How to improve primary school students’ social participation in the inclusive classroom? – Preliminary results from an intervention study. Oral Communication. Symposium “FRIEND-SHIP: A school-based intervention aimed at improving students’ social participation implemented in four countries” (Sílvia Alves). Porto International Conference on Research in Education 2022 (ICRE 2022) - Görel, Gamze; Löper, Marwin Felix; Hellmich, Frank

The relationship between primary school students’ contact experiences and their attitudes towards peers with non-compliant behaviour. Single Paper. ECER (European Conference on Educational Research) 2022 PLUS. “Education in a Changing World: The impact of global realities on the prospects and experiences of educational research” - Löper, Marwin Felix; Lehofer, Mike; Schwab, Susanne; Hellmich, Frank